Organizing the Unorganized: The Service, Office, and Retail Workers' Union of Canada (SORWUC), 1972-1986 - Smith, Julia Maureen (Simon Fraser University, 2009)
This thesis examines the Service, Office, and Retail Workers' Union of Canada (SORWUC), an independent, grassroots, socialist feminist union that organized unorganized workers in Canada in the 1970s and 1980s. It looks at SORWUC's role in Canadian labour history in general, and its efforts to organize unorganized workers in particular, focusing on SORWUC's efforts to organize workers at a pub and a restaurant in British Columbia. The central thesis of this work is that SORWUC's socialist feminist unionism and commitment to organizing unorganized workers positioned the union as radically different from much of the 1970s Canadian labour movement, and that this difference both helped and hindered the union in its efforts to organize the unorganized. By examining SORWUC from this neglected perspective, this thesis ultimately aims to demonstrate SORWUC's importance to the historiography of class and labour organizing in Canada.
Keywords: British Columbia; Canada; Labour Organizing; Labour Unions; Service Industry; Service, Office, and Retail Workers’ Union of Canada (SORWUC); Socialist Feminism